-13=-(-4x+4)+x+1

Simple and best practice solution for -13=-(-4x+4)+x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13=-(-4x+4)+x+1 equation:


Simplifying
-13 = -1(-4x + 4) + x + 1

Reorder the terms:
-13 = -1(4 + -4x) + x + 1
-13 = (4 * -1 + -4x * -1) + x + 1
-13 = (-4 + 4x) + x + 1

Reorder the terms:
-13 = -4 + 1 + 4x + x

Combine like terms: -4 + 1 = -3
-13 = -3 + 4x + x

Combine like terms: 4x + x = 5x
-13 = -3 + 5x

Solving
-13 = -3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-13 + -5x = -3 + 5x + -5x

Combine like terms: 5x + -5x = 0
-13 + -5x = -3 + 0
-13 + -5x = -3

Add '13' to each side of the equation.
-13 + 13 + -5x = -3 + 13

Combine like terms: -13 + 13 = 0
0 + -5x = -3 + 13
-5x = -3 + 13

Combine like terms: -3 + 13 = 10
-5x = 10

Divide each side by '-5'.
x = -2

Simplifying
x = -2

See similar equations:

| 7y-3y=21 | | k-4/3=10 | | 9t-6-t=6 | | 3y=3x+6 | | 3x+6=7x-6 | | 2/9(2/10-7/10) | | 7(c+3)=6+6c | | -3-2u=4 | | 3x+14/(5x)=7 | | x+3/4=8 | | 4m+15=5m-15 | | 4x^2-8x+9=3x^2-6x-11 | | x+2=7x+50 | | 17=-3(-x-3)+x-4 | | 3x+15=(x+5) | | 6t+5=35 | | 0.14(y-4)+0.12y=0.08y-0.05(40) | | -12(b-7)=-12 | | 4x^2-8x+9=3c^2-6x-11 | | m=-5/4(-1)-2 | | 10+2x=-2x+46 | | 5-(-6-I)+(i)= | | 6a+2a-0.50(4a-8)=16 | | -3(c-6)=-3c- | | 9x-14=12x-50 | | -14=-1-(4x-3) | | 10+2x=12x+46 | | 88.1-2.3h=72.46 | | 3x+14/5x=31/5 | | 5(4n+2)= | | 5x+1/8=6x+3/8 | | x/28+4x3 |

Equations solver categories